2013
DOI: 10.1038/jid.2013.222
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-Dioxygenase Activity Contributes to Local Immune Suppression in the Skin Expressing Human Papillomavirus Oncoprotein E7

Abstract: Chronic infection of anogenital epithelium with human papillomavirus (HPV) promotes development of cancer. Many pathogens evoke immunosuppressive mechanisms to enable persistent infection. We have previously shown that grafted skin expressing HPV16 E7 oncoprotein from a keratin-14 promoter (K14E7) is not rejected by a syngeneic, immunocompetent host. In this study we show that indoleamine 2, 3-dioxygenase (IDO) 1, an IFN-γ inducible immunoregulatory molecule, is more highly expressed by langerin−ve dermal dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 34 publications
1
66
0
1
Order By: Relevance
“…We have previously shown that skin grafts expressing HPV16.E7 oncoprotein are not spontaneously rejected when transplanted onto syngeneic animals, but are rejected when certain components of the innate immune system are unavailable, confirming that expression of HPV16.E7 in the epithelium results in the establishment of a local suppressive environment and the subversion of antigen specific T cells (Mattarollo et al , 2010; Mittal et al , 2013). Therefore, successful strategies targeting HPV-associated cancer need to circumvent or disrupt the local suppressive environment.…”
Section: Introductionmentioning
confidence: 76%
“…We have previously shown that skin grafts expressing HPV16.E7 oncoprotein are not spontaneously rejected when transplanted onto syngeneic animals, but are rejected when certain components of the innate immune system are unavailable, confirming that expression of HPV16.E7 in the epithelium results in the establishment of a local suppressive environment and the subversion of antigen specific T cells (Mattarollo et al , 2010; Mittal et al , 2013). Therefore, successful strategies targeting HPV-associated cancer need to circumvent or disrupt the local suppressive environment.…”
Section: Introductionmentioning
confidence: 76%
“…These can develop into myeloid-derived suppressor cells (MDSC) at the tumor site and suppress T cell responses (42). Infiltrates of myeloid cells were also observed in HPV16 E7-driven hyperplastic skin (25), suggesting an IL-17-associated recruitment of myeloid cells and their subsequent development into MDSC as a possible mechanism responsible for impaired host effector T cell responses to K14E7 skin grafts, particularly as IDO expression is elevated in CIN2/3 lesions, and in K14E7 skin, and contributes to local immune regulation (43). However, numbers of CD11b + Gr-1 int MDSC were similar in K14E7 and E7 + IL-17 −/− grafts (Supplemental Figure 3), indicating that recruitment of MDSC into E7 + skin is IL-17-independent.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, great advances have been made in understanding the role of amino acid metabolism of Arg and Trp during development of the immune response (49 -51). Hence, amino acid catabolic enzymes arginase and indoleamine 2,3-dioxygenase have been shown to have important immunoregulatory functions (52,53). BCATc is another amino acid catabolic enzyme that is described here as a novel immunoregulatory enzyme and indicates a role for Leu metabolism in the regulation of T cell metabolic reprograming.…”
Section: Discussionmentioning
confidence: 99%